2020
DOI: 10.20409/berj.2019.231
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between CO2 and Health Expenditures in BRICS-T Countries

Abstract: One of the most important indicators of deterioration in environmental quality is the increase in carbon dioxide emissions. Increasing carbon dioxide emissions negatively affect the health of individuals and lead to the emergence of a number of chronic diseases. The most significant cost of chronic diseases which reduces employee productivity is the impact on health expenditures. The purpose of this study is to investigate the relationship between carbon dioxide emissions and health expenditures for BRICS-T co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In the same direction, Owusu and Sarkodie ( 12 ) studied the influence of air pollution on disability-adjusted life years (DALYs), mortality, and welfare and they found significant positive and negative impacts of environmental pollution on health status (DALYs, premature deaths, and mortality) and economic development, respectively. Moreover, some recent research has examined the role of health expenditures in developing the population’s health status and curbing environmental degradation [e.g., ( 4 , 10 , 13–18 )]. For instance, Houeninvo ( 16 ) examined the consequences of private and public health expenditures on health status for 37 African countries and his results show that public health expenditure effectively improves health status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same direction, Owusu and Sarkodie ( 12 ) studied the influence of air pollution on disability-adjusted life years (DALYs), mortality, and welfare and they found significant positive and negative impacts of environmental pollution on health status (DALYs, premature deaths, and mortality) and economic development, respectively. Moreover, some recent research has examined the role of health expenditures in developing the population’s health status and curbing environmental degradation [e.g., ( 4 , 10 , 13–18 )]. For instance, Houeninvo ( 16 ) examined the consequences of private and public health expenditures on health status for 37 African countries and his results show that public health expenditure effectively improves health status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gas and oil consumption has no significant impact on Health. Erdoğan et al( 2019 ) Turkey 1971–2016 Johansen co-integration, DOLS In LR, 1% increase in CO 2 decreases life exp. by 0.14 and increases infant mortality rate by 0.19 %.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A unidirectional causal relationship between CO 2 emissions and healthcare expenditures was validated through various studies such as Chaabouni and Saidi [ 18 ], Erdogan et al (China) [ 58 ] since other studies identified a bidirectional causality [ 8 , 18 ] or no significant causality [ 58 ].…”
Section: Empirical Analysismentioning
confidence: 99%